Revision Hip Arthroscopy in the Native Hip: A Review of Contemporary Evaluation and Treatment Options - Kunze, Kyle N.; Olsen, Reena J.; Sullivan, Spencer W.; Nwachukwu, Benedict U. (Frontiers in Surgery, 2021)
Hip arthroscopy is a reproducible an efficacious procedure for the treatment of femoroacetabular impingement syndrome (FAIS). Despite this efficacy, clinical failures are observed and are challenging clinical entities to treat and may require revision hip arthroscopy. The most common cause of symptom recurrence after hip arthroscopy that leads to a revision arthroscopy is residual cam morphology as a result of inadequate femoral osteochondroplasty and restoration of head-neck offset, though several other revision etiologies including progressive chondral and labral pathologies also exist. In these cases, it is imperative to perform a comprehensive examination to identify the cause of a failed primary arthroscopy as to assess whether or not a revision hip arthroscopy procedure is indicated. When a secondary procedure is indicated, approaches may consist of revision labral repair, complete labral reconstruction, or labral augmentation depending on labral integrity. Gross instability or imaging-based evidence of microinstability may necessitate capsular augmentation or plication. If residual cam or pincer morphology is present, additional resection of the osseous abnormalities may be warranted. This review discusses indications, the evaluation of patients with residual symptoms after a primary hip arthroscopy, and evaluation of outcomes following revision hip arthroscopy through an evidence-based discussion. We also present a case example of a revision hip arthroscopy procedure to highlight necessary intraoperative techniques during a revision hip arthroscopy.